Analysis of improved nutritional composition of potential functional food (Okara) after probiotic solid-state fermentation - Gupta, Sulagna (2020)
Okara is a major agro-waste, generated as a byproduct from the soymilk and tofu industry. Since okara has a high nutritive value, reusing it as a substrate for solid state biofermentation is an economical and environmental friendly option. Rhizopus oligosporus and Lactobacillus plantarum were the probiotic FDA-approved food-grade cultures used in this study. The study revealed that biofermenting okara improves its nutritional composition. It was found that the metabolomic composition (by GC-MS analysis) and antioxidant activity (by DPPH test) improved after the microbial fermentations. Of the two, okara fermented with R. oligosporus showed better results. Further, the metabolites were traced back to their respective biosynthesis pathways, in order to understand the biochemical reactions being triggered during the fermentation processes. The findings of this entire work open up the possibility of employing fermented okara as a potential functional food for animal feed.